Sex Differences in Emergent Literacy and Reading Behaviour in Junior Kindergarten. (March 2018) - Deasley, Shanna; Evans, Mary Ann; Nowak, Sarah; Willoughby, David
In a sample of 128 Canadian junior kindergarten children (66 boys), we examined sex differences in emergent literacy and behaviour when listening to and interacting with books of four types: alphabet books with simple text and illustrations, traditional alphabet books with complex text and illustrations, alphabet eBooks, and illustrated storybooks. Girls outperformed boys on tests of emergent literacy. Engagement while listening to books being read was highest for storybooks but there was a sex by condition effect: Boys were less engaged with complex alphabet books than the other book types, whereas girls were less engaged with simple alphabet books than storybooks. During independent reading, both sexes spent significantly more time on-task in the eBook condition but less of their activity involved letter-related behaviours (e.g., saying letter names). Boys spent less time involved in letter-related behaviour than girls. This research contributes to identifying and promoting factors related to early academic success.